The criminalization of hate: A social constructionist analysis. - Janhevich, Derek E. (University of Ottawa (Canada), 1997)
The concept of "hate" within the criminal justice system is one that has recently come under much scrutiny by academics, lawyers, the media, law enforcement, public policy, lobbyists, and other affected groups. This thesis is a study on the social construction of "hate"--as it pertains to the criminal justice system. The theoretical framework guiding this thesis is rooted in social constructionism as espoused in the works of Joel Best and Malcolm Spector and John Kitsuse. Two central themes are typification and claimsmaking. Essentially, the focus is on the different ways in which hate has been typified since its inception in the criminal justice system more than thirty years ago, and how different claimsmakers have brought the issue to the fore. Three major phases are described with three different typifications of hate: (1) Hate Propaganda; (2) Hate-motivated Violence; and (3) Hate Crimes. The thesis demonstrates how advocacy groups, academia, the police, and the media have all played a fundamental role in problematizing and criminalizing "hate". (Abstract shortened by UMI.)
Keywords: Sociology, Criminology and Penology.